E-Government Integrated E-Audit System : Design And Analysis in The Internal Audit Unit of The Indonesian Government (APIP) - Deni Hidayat (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
The Government Internal Supervisory Agency (APIP) is a work unit that has the task of carrying out internal supervision in the government environment. The development of the Electronic Based Government System (SPBE) has changed the business processes that occur in government governance from manual to digital form. The implementation of SPBE in government activities has resulted in a lot of data or documents in digital form, but on the other hand the process of implementing audit activities carried out by APIP is currently still being carried out manually, has not made much use of digital data or documents, and has not been supported by the use of an integrated audit management information system. This study aims to design an integrated electronic-based audit system model (e-Audit) with SPBE in the APIP environment. The research method used is qualitative with a case study approach in one of the Inspectorates of Non-Ministry Government Institutions, the result of this research is an integrated e-audit system model which is described in a System Context Diagram, Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD).